The response of introduced initial material to dry conditions - G. Ya. Krivosheev; A. S. Ignatiev; A. G. Gorbacheva; I. A. Vetoshkina (Зерновое хозяйство России, 2018)
Here has been carried out the study of ten parental forms of maize hybrids in moisture supplied conditions (All-Russian RI of maize, Pyatigorsk) and in dry conditions (All-Russian RI of Grain crops, Zernograd) according to the main economic-valuable traits, i.e. grain productivity, harvesting moisture of grain, a length of the period ‘sprouts-flowering’, lodging, infection with blister smut, infertility, a plant height and a height of cob attachment. The moisture supply differed in 2014 and 2016 that resulted in significant decrease of average productivity of the studied form in a dry trial. In 2015 the same moisture conditions in both trials resulted in the same amount of productivity of the studied forms. There have been determined such parental forms with high indexes of drought tolerance as ‘Istok S’(36.0%), ‘Mirt M’(44.9%), ‘Malvina S’(39.3%), ‘Verbena SD’(39.2%) and ‘Maya M’(39.7%). They are characterized with high indexes of main economic-valuable traits in dry conditions: grain productivity of 3.16-4.41 t/ha, harvesting moisture of grain of 11.3-14.9%, a height of cob attachment of 78.0-87.0cm, infection with blister smut 0-2.2%, lodging of 0.3-3.7%. The obtained parental forms are the promising ones for maize hybridization in the Rostov region characterized with unstable humidity. The correlation between an index of drought tolerance and plant infertility has been established. It has been recommended to use the data received in the years with contrast moisture supply for calculation of the index of drought tolerance.